Water intake, faecal output and intestinal motility in horses moved from pasture to a stabled management regime with controlled exercise. (21st March 2014) - Williams, S.; Horner, J.; Orton, E.; Green, M.; McMullen, S.; Mobasheri, A.; Freeman, S. L.
Summary Reasons for performing study A change in management from pasture to stabling is a risk factor for equine colic. Objectives To investigate the effect of a management change from pasture with no controlled exercise to stabling with light exercise on aspects of gastrointestinal function related to large colon impaction. The hypothesis was that drinking water intake, faecal output, faecal water content and large intestinal motility would be altered by a transition from a pastured to a stabled regime. Study design Within‐subject management intervention trial involving changes in feeding and exercise using noninvasive techniques. Methods Seven normal horses were evaluated in a within‐subjects study design. Horses were monitored while at pasture 24 h/day, and for 14 days following a transition to a stabling regime with light controlled exercise. Drinking water intake, faecal output and faecal dry matter were measured. Motility of the caecum, sternal flexure and left colon (contractions/min) were measured twice daily by transcutaneous ultrasound. Mean values were pooled for the pastured regime and used as a reference for comparison with stabled data (Days 1–14 post stabling) for multilevel statistical analysis. Results Drinking water intake was significantly increased (mean ± s.d. pasture 2.4 ± 1.8 vs. stabled 6.4 ± 0.6 l/100 kg bwt/day), total faecal output was significantly decreased (pasture 4.62 ± 1.69 vs. stabled 1.81 ± 0.5 kg/100 kg bwt/day) and faecal dry matter content was significantly increased (pasture 18.7 ± 2.28 vs. stabled 27.2 ± 1.93% DM/day) on all days post stabling compared with measurements taken at pasture (P<0.05). Motility was significantly decreased in all regions of the large colon collectively on Day 2 post stabling (‐0.76 contractions/min), and in the left colon only on Day 4 (‐0.62 contractions/min; P<0.05). Conclusions There were significant changes in large intestinal motility patterns and parameters relating to gastrointestinal water balance during a transition from pasture to stabled management, particularly during the first 5 days.